2018
DOI: 10.7759/cureus.2304
|View full text |Cite
|
Sign up to set email alerts
|

Fahr’s Disease: A Differential to Be Considered for Various Neuropsychiatric Presentations

Abstract: Fahr’s disease, also known as familial idiopathic basal ganglia calcification, is a neurodegenerative disorder affecting cerebral microvessels, mainly the basal ganglia, and presenting with diverse neuropsychiatric manifestations. It is considered to be mainly hereditary, with autosomal dominant inheritance. In light of its various presentations and incomplete penetrance, Fahr’s disease is known to be underestimated and underdiagnosed. Here, an early-onset case of Fahr’s disease is presented mainly with pure p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…[ 7 ] About 40% of patients with BG calcification show neuropsychiatric manifestations. [ 7 ] Cortico-subcortical disconnection due to BG calcification involves frontostriatal and limbic pathways[ 7 17 18 ] resulting in psychosis, mood, personality, and cognition disorders. In our study, we found that depression (23.1%) was the most common neuropsychiatric manifestation in FD followed by anxiety disorder (15.4%) and psychosis (7.7%).…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] About 40% of patients with BG calcification show neuropsychiatric manifestations. [ 7 ] Cortico-subcortical disconnection due to BG calcification involves frontostriatal and limbic pathways[ 7 17 18 ] resulting in psychosis, mood, personality, and cognition disorders. In our study, we found that depression (23.1%) was the most common neuropsychiatric manifestation in FD followed by anxiety disorder (15.4%) and psychosis (7.7%).…”
Section: Discussionmentioning
confidence: 99%
“…There are some suggestions that intracerebral calcium deposition is secondary to local disturbance of the bloodbrain barrier or neuronal calcium metabolism disorder. 29 An important argument in favor of vascular theory was given by studies using cerebral flow scintigraphy that provided evidence of altered blood flow to the calcification sites. 30 Furthermore, inflammatory conditions, such as meningitis or encephalitis, are considered in pathogenesis of Fahr's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline biochemical investigations are indicated to rule out other possible diagnoses (Table 4) [7-8].…”
Section: Discussionmentioning
confidence: 99%